Increasing the Students Ability in Vocabulary Mastery by Using Flash Card at the Eighth Grade of SMP Negeri 1 Gido in 2022/2023 - Zalukhu, Sarmin; Harefa, Afore Tahir; Waruwu, Yaredi (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The lack of English vocabulary mastery becomes a problem for SMP Negeri one Gido. The purpose of this research is to increase the student’s ability in vocabulary mastery by using Flash Card. The research was conducted using quantitative methods. The subject of the research was the students in SMP Negeri one Gido in two thousand twenty-two to two thousand twenty-three. The research has been conducted in two cycles, in which each cycle consisted of two meetings, There were four steps in conducting this research namely: Planning, Action, Observation, and Reflection. Then the researcher used observation sheet, evaluation sheet, and field notes to collect the data. From the result of the research in each cycle, it has been shown that the students improved through Flash Card. In Cycle I the average of the students’ values was fivety two. Because the result was not satisfying, so the research is continued to Cycle II by considering the weaknesses of Cycle I. In Cycle II the average of the students’ values was eighty. Based on the analysis of research findings, it can be concluded that Flash Card can increase the student's ability in mastering vocabulary in reading descriptive text and recommended to be applied in school.